2011
DOI: 10.1017/s0967199411000141
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression and developmental competence inin vitroproduced bovine embryos

Abstract: The embryonic developmental block occurs at the 8-cell stage in cattle and is characterized by a lengthening of the cell cycle and an increased number of embryos that stop development. The maternal-embryonic transition arises at the same stage resulting in the transcription of many genes. Gene expression studies during this stage may contribute to the understanding of the physiological mechanisms involved in the maternal-embryonic transition. Herein we identified genes differentially expressed between embryos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…In bovine, fast development in vitro embryo production (IVP) embryos have been found to display higher blastocyst conversion, lower developmental block and better quality regarding programmed cell death, when compared with slow development embryos, a similar phenotype to those found when antioxidants are added to the individually in vitro-cultured (IVC) cells (Garcia et al, 2015;Silva et al, 2016;Zullo et al, 2016;dos Santos et al, 2019). At the embryonic genome activation period (8-16 cells), fast development embryos also seem to activate genes related to development, whereas the slow ones activate genes related to cell survival and apoptosis (Ripamonte et al, 2012). However, how lipid metabolism occurs in embryos with different speed of development is unknown.…”
Section: Introductionmentioning
confidence: 79%
“…In bovine, fast development in vitro embryo production (IVP) embryos have been found to display higher blastocyst conversion, lower developmental block and better quality regarding programmed cell death, when compared with slow development embryos, a similar phenotype to those found when antioxidants are added to the individually in vitro-cultured (IVC) cells (Garcia et al, 2015;Silva et al, 2016;Zullo et al, 2016;dos Santos et al, 2019). At the embryonic genome activation period (8-16 cells), fast development embryos also seem to activate genes related to development, whereas the slow ones activate genes related to cell survival and apoptosis (Ripamonte et al, 2012). However, how lipid metabolism occurs in embryos with different speed of development is unknown.…”
Section: Introductionmentioning
confidence: 79%
“…; Ripamonte et al . ). It is demonstrated that melatonin not only directly inhibits the mitochondrial permeability transition pore opening, but also prevents the release of cytochrome c from mitochondria to inhibit caspase activation and apoptosis (Asghari et al .…”
Section: Discussionmentioning
confidence: 97%
“…The exact reasons for this low efficiency are not known but have been investigated extensively in terms of genomic reprogramming. The results of these studies indicate complex changes in the patterns of epigenetic processes, especially in cloned embryos, including reduced expression of genes such as FGF4, NANOG, CASP genes and those responsible for trophoblast differentiation, and overexpression of IFNT and genes coding for angiogenetic factors, among others (Mundim et al 2009;Campos et al 2010;Rodríguez-Alvarez et al 2010;Leidenfrost et al 2011;Ripamonte et al 2011;Gong et al 2012).…”
Section: Introductionmentioning
confidence: 99%